Association between exposure to outdoor artificial light at night and the risk of preterm birth - Sun, Qi; Yang, Yang; Liu, Jing; Ye, Fang; Chen, Yuanmei; Liu, Die; Zhang, Qi (Frontiers in Public Health, 2023)
Background This study aimed to investigate the association between outdoor artificial light at night (ALAN) exposure during pregnancy and the risk of preterm birth (PTB). Methods A retrospective case–control study was conducted, and data were collected from pregnant women residing in Beijing, China. The level of ALAN exposure during pregnancy was estimated using remote sensing satellite data. Propensity score matching was utilized to match the control group. Logistic and multivariate linear regression were used to analyze the association between ALAN and the risk of PTB. The odds ratio (OR) and partial regression coefficient (β) with 95% confidence interval (CI) were utilized to assess the association. Results A total of 2,850 pregnant women were enrolled in this study. ALAN (nW/cm2/sr) exposure was higher in the PTB group than in the control group during first trimester (mean ± standard deviation: 25.30 ± 17.91 vs. 17.56 ± 14.74, p < 0.001) and second trimester (27.07 ± 18.10 vs. 21.93 ± 16.08, p < 0.001). A negative association was found between ALAN exposure and gestation day in the first (β = −0.151, 95%CI: −0.217 to −0.085, p < 0.001) and second trimesters (β = −0.077, 95%CI: −0.139 to −0.015, p = 0.015). ALAN was identified as a risk factor for PTB during the first trimester (OR = 1.032, 95%CI: 1.025–1.040, p < 0.001) and the second trimester (OR = 1.018, 95%CI: 1.011–1.025, p < 0.001), while no significant association was observed in the third trimester. Conclusion Our study suggesting that exposure to outdoor ALAN, especially during first and second trimester, was associated with the risk of PTB. These findings highlight the potential impact of ALAN on pregnancy health and offer new insights into the risk of PTB.